2017
DOI: 10.5812/ijem.57897
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in Thyroid Cancer

Abstract: BackgroundThe number of studies on venous thromboembolism (VTE) and thyroid cancer is very scarce and existing data are contradictory. This paper reviews VTE in thyroid cancer.MethodsThe following words were used for a comprehensive literature review using MEDLINE database: Blood coagulation factors; thyroid hormones; blood coagulation tests; venous thromboembolism; receptors thyroid hormone; hemostasis; fibrinolysis; bleeding; blood coagulation disorders; thyroid neoplasms; Thyroid cancer, papillary; Thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…A series of related studies had reported changes in the coagulation status of PTC patients, suggesting a relatively hypercoagulable state for PTC patients, mainly evaluated by changes of fibrinogen and related coagulation factor levels [15][16][17]. Nielsen et al had once reported a patient with a malignant thyroid tumor who was serendipitously found to have plasmatic hypercoagulability with a carbon monoxide-mediated clot strength as determined by a thrombelastographic method [18].…”
Section: Introductionmentioning
confidence: 99%
“…A series of related studies had reported changes in the coagulation status of PTC patients, suggesting a relatively hypercoagulable state for PTC patients, mainly evaluated by changes of fibrinogen and related coagulation factor levels [15][16][17]. Nielsen et al had once reported a patient with a malignant thyroid tumor who was serendipitously found to have plasmatic hypercoagulability with a carbon monoxide-mediated clot strength as determined by a thrombelastographic method [18].…”
Section: Introductionmentioning
confidence: 99%
“…The significance and pathogenic mechanisms of platelet clustering in adenomas and in vessels not associated with tumor cells is unknown. This finding may be due to a local prothrombotic effect in the tumor milieu or procedurerelated vascular microtrauma leading to thrombosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Rate of expression was not different by tumor type (p = 0.90; Table 1). Of the 22 positive cases, the location of vessels containing CD61-positive intravascular platelets was peritumoral in 60% (13), intracapsular in 23% (5), and distant in 9% (2). The location of vessels was not different by tumor type (p > 0.6; Table 1).…”
Section: Cd61 Expressionmentioning
confidence: 93%
“…This may also apply to patients with thyroid carcinoma whose endogenous thyrotropin post-thyroidectomy is under suppression with exogenous T 4 in greater than replacement dosage. 56 Evaluation might initially involve measurement of widely available activated partial thromboplastin time (aPTT) and the D-dimer fibrin degradation product at the time of diagnosis of thyroid disease.…”
Section: Discussionmentioning
confidence: 99%